2017
DOI: 10.1177/0011392117737819
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting individualization: The transitions to marriage and motherhood in Chile

Abstract: The life course of Chilean women has experienced profound transformations in the past decades. It has been argued that transitions to marriage and motherhood are being postponed as they are experienced by women at an older age and are becoming events that characterize an increasingly smaller part of the female population. These changes have been often interpreted as part of a process of individualization that would have had reconfigured the cultural norms and social practices regarding gender roles and family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Likewise, marriage is becoming less frequent. The life course of Chilean women is increasingly individualized, although this process is conditioned to the social structure (educational level and the profession) (Gómez-Urrutia & Royo, 2016;Yopo, 2017). Besides, Chilean women have less control capacity in the material and political area, lower wages, and fewer labor opportunities (Franceschet et al, 2015;Guzmán et al, 2012;Hermans et al, 2016;Mora & Blanco 2017;Ugarte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, marriage is becoming less frequent. The life course of Chilean women is increasingly individualized, although this process is conditioned to the social structure (educational level and the profession) (Gómez-Urrutia & Royo, 2016;Yopo, 2017). Besides, Chilean women have less control capacity in the material and political area, lower wages, and fewer labor opportunities (Franceschet et al, 2015;Guzmán et al, 2012;Hermans et al, 2016;Mora & Blanco 2017;Ugarte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The literature describes an exponential increase in egalitarian attitudes starting in the 1970s (Blofield & Martínez, 2015;Cotter et al, 2011;Pedulla & Thebaud, 2015;Pepin & Cotter, 2018;Scarborough et al, 2018;Walter, 2018;Yopo, 2017). Unfortunately, we are experiencing a slow-down in change, and the revolution in gender roles is incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beck (2007) criticized sociology for its ‘methodological nationalism’, which conflates social structure and the nation-state – a view which, he argued, could not be supported in the age of globalization. The main response of sociologists was to reinstitute the significance of the nation-state by demonstrating local variations of social patterns between countries (Brückner and Mayer, 2005; Buchmann and Kriesi, 2011; Mayer, 2009; Mills and Blossfeld, 2006; Shanahan, 2000; Yopo Díaz, 2018). Our findings suggest that global forces are expressed differently not only between countries, but also within them.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, scholarly attention has shifted from universal explanations to more nuanced accounts of various patterns of entering adulthood in different countries (Brückner and Mayer, 2005; Buchmann and Kriesi, 2011; Mayer, 2009; Shanahan, 2000; Yopo Díaz, 2018). Mills and Blossfeld (2006), for example, suggested that the uncertainties created by globalization are filtered through national welfare regimes and specific employment, educational and family systems.…”
Section: The Changes In Life Course Transitionsmentioning
confidence: 99%